PENGARUH RELATIONSHIP MARKETING DAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH BMT NU CABANG JOMBANG - Maulida Dini Karimah; Khotim Fadhli (Institut Pendidikan Tapanuli Selatan, 2024)
As time progresses and competitors become increasingly stringent in all financial institutions, especially those related to institutions providing financial services. In its steps, BMT NU Jombang Branch is required to continue to develop so it is needed. BMT NU Jombang Branch is an institution that operates in the service sector, so customer satisfaction requires research to be ensured. This research aims to determine the effect of relationship marketing and customer satisfaction on customer satisfaction using quantitative research methods using multiple linear regression tests where the sample used in this research is 100 respondents. The results of this research state that relationship marketing has no effect on customer satisfaction, while service quality has a positive effect on customer satisfaction. Relationship marketing and service quality have a simultaneous positive effect on customer satisfaction at BMT NI Jombang Branch.